DESIGN OF AN INTERNET OF THINGS (IoT) ON A SINGLE SLOPE SOLAR STILL MONITORING SYSTEM USING A FINITE STATE MACHINE (FSM) - Dea Nurul Khumairoh; Eko Budiraharjo; Sunardi Sunardi; Agus Wibowo; Irfan Santosa (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2026)
In addition to distilled water productivity, the single-slope solar still (S4) faces issues with temperature and solar intensity measurement devices, which are relatively expensive. Therefore, this study aims to design and implement an Internet of Things (IoT)-based S4 monitoring system using an ESP32 microcontroller so that distillation parameters can be monitored automatically and in real time. Sensor data is displayed on an LCD and transmitted to the Blynk app for real-time monitoring. The Finite State Machine (FSM) method is used to control the LCD, while non-blocking scheduling is applied for periodic data acquisition. Test results show that the system functions properly and that the DS18B20 sensor provides accurate measurements. The developed system serves as an effective solution for real-time monitoring of temperature and solar intensity parameters in the S4 Still.